2013
DOI: 10.1088/0004-637x/770/1/21
|View full text |Cite
|
Sign up to set email alerts
|

THE WIRED SURVEY. IV. NEW DUST DISKS FROM THE McCOOK & SION WHITE DWARF CATALOG

Abstract: We have compiled photometric data from the Wide-field Infrared Survey Explorer All Sky Survey and other archival sources for the more than 2200 objects in the original McCook & Sion Catalog of Spectroscopically Identified White Dwarfs. We applied color-selection criteria to identify 28 targets whose infrared spectral energy distributions depart from the expectation for the white dwarf photosphere alone. Seven of these are previously known white dwarfs with circumstellar dust disks, five are known central stars… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 108 publications
(109 reference statements)
1
37
0
Order By: Relevance
“…In addition to which, the temperatures for the observed dust discs are generally significantly hotter than 700K (e.g. Hoard et al 2013). We, therefore, conclude that the absence of infrared excesses is unlikely to be explained by the discs being cool.…”
Section: Inner Temperature Tinmentioning
confidence: 65%
“…In addition to which, the temperatures for the observed dust discs are generally significantly hotter than 700K (e.g. Hoard et al 2013). We, therefore, conclude that the absence of infrared excesses is unlikely to be explained by the discs being cool.…”
Section: Inner Temperature Tinmentioning
confidence: 65%
“…This catalog has been also used to search for dusty disks around WDs (Hoard et al 2013) using WISE observations. However in this sample the number of sources detected at 3.4µm, 4.6µm and 12µm for which is possible to built the mid-IR colors is only 91.…”
Section: White Dwarfsmentioning
confidence: 99%
“…We find that WD 0420+520 is surrounded by a thin, 0.05 R wide, dusty disc. This object was first identified as a candidate WD+disc system using WISE by Hoard et al (2013) and was recently found to have Ca absorption lines in its Keck+HIRES spectrum (Debes, private communication). There is a blended source in the IRAC Ch 1 photometry, but is cleanly subtracted (Fig.…”
Section: New Discsmentioning
confidence: 99%